MENINGKATKAN KREATIFITAS SISWA KELAS XI MELALUI EKSTRAKUTIKULER DESAIN GRAFIS DI SMA MAMBAUNNUR GADING BULULULAWANG MALANG - Nur Qomari; Muhammad Hasbulloh Huda (LP3M IAI Al-Qolam, 2021)
This study focuses on creative characters building through graphic design extracurriculars. This research is motivated by the increasingly advanced era and increasingly sophisticated technology, students have high talent and ability to develop talents, especially students who have in the field of art. The research questions are “how to build the creative character of class XI students through graphic design extracurriculars, and what are the supporting and inhibiting factors for the formation of creative characters of class XI students through graphic design extracurriculars at SMA Mamba'unnur Gading Bululawang”. It is qualitative research, that uses observation, interview, and documentation to collect data. Qualitative data analysis lies in the presentation of what has been produced from the research process. After that, a comprehensive and in-depth conclusion or problem emerges. The results of the study show that the formation of creative characters at Mamba'unnur High School through graphic design extracurriculars uses classical methods in delivering material, habituation methods and discipline methods in doing assignments, so that not only creative characters appear, but students also have the character of responsibility and discipline. On the other hand, there are also supporting and inhibiting factors in the formation of student character, including the ability factor of students, as well as environmental factors and friends' associations.